Persepsi yang Mendasari Proses Aktualisasi Diri melalui Facebook - Ade Arianto Cipto Putra; Vincentius Vincentius (Politeknik Negeri Batam, 2012)
Facebook is one of social media, by use it, we could communicate about ours idea and share about ours life. Facebook purpose is like autobiography, written a journey of life and describes a word what have incurred on every day. Self actualization is a main of what we want to do on Facebook. Perception on self actualization need to be connected in order to minimize negative communication.